Age at first birth, age at menopause, and risk of ovarian cyst: a two-sample Mendelian randomization study - Su, Qian; Yang, Zhiyong (Frontiers in Endocrinology, 2024)
Background Increasing observational studies have indicated that hormonal reproductive factors were associated with ovarian cyst, a common gynecological disease. A two-sample Mendelian randomization (MR) was carried out by investigating the causality of reproductive factors including age at first birth (AFB), age at natural menopause (ANM), and age at menarche (AAM), and the risk of ovarian cyst (OC). Method Summary statistics were collected from a large genome-wide association study (GWAS), and we used a two-sample MR study to clarify the causal association between the exposure of AFB (N = 542,901), ANM (N = 69,360), and AAM (N = 29,346) and the outcome of the OC (Ncase = 20,750, Ncontrol = 107,564). We separately selected 51, 35, and 6 single-nucleotide polymorphisms (SNPs) as instrumental variables (IVs) for assaying the influence of AFB, ANM, and AAM on OC, respectively. Then, the causal relationship was tested through multiple approaches including an inverse-variance weighted method, an MR-Egger regression, and a weighted median method. In addition, the MR-PRESSO method was also used to verify the horizontal pleiotropy. Subsequently, we adjust the confounders for MR design. Results The MR analysis results showed that AFB was negatively associated with the OC (IVW Beta: −0.09, OR: 0.91, 95% CI: 0.86–0.96, p = 0.00185), and the greater AAM decreased the risk of OC (IVW Beta: −0.10, OR: 0.91, 95% CI: 0.82–0.99, p = 0.0376). However, ANM has a positive correlation with the OC (IVW Beta: 0.05, OR: 1.05, 95% CI: 1.03–1.08, p = 8.38 × 10−6). After adjusting BMI, alcohol intake frequency, and ever smoked, we also obtained a negative relationship between AFB and OC (p < 0.005). Meanwhile, we adjusted weight, alcohol intake frequency, and height, and then found a causal relationship between older AMN and an increased risk of OC (p < 0.005). Conclusion A causal effect of reproductive factors on the development of OC, affected by AFB, ANM, and AAM, was found convincingly. After adjusting the confounders, we also successfully found the substantial causal effect of younger AFB, younger AAM, and older ANM on an increased risk of OC.